Retroperitoneal laparoscopic nephroureterectomy with distal and intramural ureter resection for a tuberculous non - functional kidney - Canqiang Li (International Brazilian Journal of Urology)
ABSTRACT Objective: To evaluate the safety and feasibility of total retroperitoneal laparoscopic nephroureterectomy with urinary-bladder junction resection for a tuberculous nonfunctional kidney. Materials and Methods: A total of 27 individuals diagnosed with unilateral nonfunctional kidney secondary to tuberculosis were treated between June 2011 and June 2015. All patients had normal renal function on the contralateral side and underwent the standard four-drug anti-tuberculosis treatment for at least four weeks before surgery. Total retroperitoneal laparoscopic nephroureterectomy was performed in all patients, and the urinary-bladder junction of distal ureter was managed using different auto-suture techniques. Results: Nineteen male and 8 female patients with an average age of 47.3 years (range, 36-64 years) underwent surgery. All the operations were successfully performed without conversion. The median operative time was 109.3 min (range, 75-138 min), the median blood loss was 157.5 mL (range, 70-250 mL), and the median hospitalization time was 3.7 days (range, 3-6 days). No serious perioperative complications occurred. Anti-tuberculosis chemotherapy was prescribed to all patients, with the entire course of treatment lasting six months. No recurrence of tuberculosis of the bladder or the contralateral kidney was observed during the median follow-up period of 26.7 months (range, 6-54 months). Conclusion: Retroperitoneal laparoscopic nephroureterectomy with urinary-bladder junction resection is a safe and feasible approach for the treatment of tuberculous non-functional kidneys.